Globalizacja a nowe koncepcje zarządzania przedsiębiorstwem - Szymańska, Anna Irena (Przedsiębiorczość - Edukacja, 2012)
Rapid globalisation of the economy, a revolution in the technical and information technology fields as well as a great variety of solutions provided nowadays by contemporary management makes the company management of XXI century to be predominantly concentrated on external environment of organization. This management should consist in defining the objectives of organisation in connection with the market needs and an individual customer. On the other hand, the economic, political and social processes taking place on a global scale force enterprises to also perform internal reorganisations.Currently a number of various concepts of organisation management and detailed methods connected with them, techniques and tools, are applied in business activities. They can be divided into three groups: • Concepts concentrated on organisation management process - marketing, logistics (just-in–time production and just-in-time management), human resources management, TQM total quality management, controlling, outsourcing, time based management (TBM), • Concepts concentrated mainly on changes management - BPR business process reengineering, lean management, • Concepts concentrated on organisation forms - learning organisation, intelligent organisation, network organisation, virtual organisation.All these theories are distinguished by different attitudes towards organisation management and changes implementation. The managers and their ability to predict the results of the applied solutions are those who choose one particular concept or certain integrated attitude.